2014
DOI: 10.1152/jn.00393.2013
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence moderates neural responses to monetary reward and punishment

Abstract: Hawes DR, DeYoung CG, Gray JR, Rustichini A. Intelligence moderates neural responses to monetary reward and punishment. J Neurophysiol 111: 1823-1832, 2014. First published February 12, 2014 doi:10.1152/jn.00393.2013The relations between intelligence (IQ) and neural responses to monetary gains and losses were investigated in a simple decision task. In 94 healthy adults, typical responses of striatal blood oxygen level-dependent (BOLD) signal after monetary reward and punishment were weaker for subjects with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(28 reference statements)
0
8
1
Order By: Relevance
“…A correlation between caudate size and intelligence is well situated in literature that supports a role for the caudate in learning, particularly in relation to the prediction-error learning signal that is transmitted by dopamine [Bromberg-Martin et al, 2010;Cools et al, 2008;Hawes et al, 2014]. Nonetheless, a limitation of the present findings is that they are purely correlational and provide no evidence regarding a mechanism for the influence of caudate volume on intelligence.…”
Section: Figurecontrasting
confidence: 46%
“…A correlation between caudate size and intelligence is well situated in literature that supports a role for the caudate in learning, particularly in relation to the prediction-error learning signal that is transmitted by dopamine [Bromberg-Martin et al, 2010;Cools et al, 2008;Hawes et al, 2014]. Nonetheless, a limitation of the present findings is that they are purely correlational and provide no evidence regarding a mechanism for the influence of caudate volume on intelligence.…”
Section: Figurecontrasting
confidence: 46%
“…Of particular relevance to the present study, one fMRI study found that neural activity in the lateral PFC during a working memory task predicted both TD and intelligence assessed outside the scanner . Further, IQ has been linked to both the functional reward response and the anatomical volume of the caudate nucleus in the striatum (Grazioplene et al, 2015;Hawes et al, 2014). The association of IQ with the caudate may reflect that Intelligence modulates how prediction-error signals in this region respond to the perceived statistical features of the environment, given that higher intelligence is likely to afford enhanced evaluation of the context of reward.…”
Section: Introductionmentioning
confidence: 99%
“…This may also contribute to the higher mean response times seen in the "ambiguous" group compared with both the "honest" and "dishonest" groups in both the win and loss trials, as well as the slower reaction times observed during dishonest behavior (Abe and Greene, 2014). Also, in a result from Hawes et al (2014), subjects with higher IQ exhibited weaker striatal BOLD signals after the reward was received, which is not inconsistent with the results in Abe and Greene (2014). This shows that sophistication has a role in the biology of decision-making (Coricelli and Nagel, 2009).…”
mentioning
confidence: 99%
“…There is recent evidence suggesting that subjects with higher IQ base their decisions in a current trial on a greater number of past trials than subjects with low IQ (Hawes et al, 2014). Those who wish to strategically underreport their accuracy on trials with low-value outcomes would require the sophistication of basing their decisions on a great number of trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation